Assessing the nutritional status of elderly in the selected municipalities of Chitwan district, Nepal - Kumar Poudyal, Jiwan; Parajuli, Sumitra; Khatun, Sahera; Prasad Dhungana, Govinda (Journal of Chitwan Medical College, 2024)
Background: Increasing the number of elderlies, the nutritional status is also an emerging issue and plays a crucial role in daily activities and non-communicable diseases. The main objective of this study was to assess the nutritional status of elderly in municipalities of Chitwan District. Method: An analytical cross-sectional study design was used to assess the nutritional status of elderly. Probability Proportion to Size sampling method was used to select sample. A total of 442 elderly recruited from community and collected data by using Mini-Nutritional Assessment standard tool and self-constructed socio-demographic questionnaire. Descriptive and inferential statistics were used to analyze data in SPSS 20 version. Result: Among 442 elderly participants, 215 were male and rest (227) female and the mean age was 70.6±7.7 years. Almost half of participants were from Brahmin/Chettri ethnic group and the highest number (72%) followed Hinduism and were illiterate. Almost four-fifths (77.8%) of participants were living with their son/daughter-in-law and their main household income was agriculture. Three-fifths of participants were at risk of malnutrition on screening (65.4%) and nutritional assessment (59.3%). There was a significant association of nutritional status with age (p<0.001), cast/ethnicity (p<0.041), chronic diseases (p<0.001), family type (p<0.003), and education (p<0.034) of participants. The participants currently ill were twice more likely to be at risk of malnutrition or malnourished than not being ill (OR: 2.319, 95%CI: 1.534-3.505). Conclusion: With the increasing age of respondents there was an increased risk of malnutrition. Brahmin/Chettri were the more at risk. Those who were suffering from chronic diseases, and were illiterate had a higher risk of malnutrition.